Analysis of the Effect of Work Shifts on the Fatigue Level of Operators of Balikpapan City Drinking Water Area Companies - Muhammad Hasyim Tuankotta; Wahyu Ismail Kurnia; Serli Yana Purwaningsih; Maslina Maslina; Padyo Budi (Journal of Industrial System Engineering and Management, 2022)
This study aims to investigate the effect of work shifts on the level of fatigue experienced by the operators of the production department of the Balikpapan City Regional Drinking Water Company (PDAM). This research is a type of quantitative research using a cross-sectional approach. The number of samples of this study was 60 operators of the balikpapan city PDAM production department spread across 6 working areas of Balikpapan City. data collection techniques by means of observation, interviews and dissemination of questionnaires. While data processing and analysis using simple linear regression analysis with the help of SPSS softwere version 22. The results showed that there was a positive and significant effect of work shifts on fatigue experienced by the operators of the production department of the Balikpapan City Regional Drinking Water Company (PDAM). The contribution of the effect of work shifts on operator work fatigue was 24.6%.